2D coordination polymer composed of 1D NiII(μ-O)(μ-H2O)NiIIn ferromagnetic chains: Modulation of magnetic properties based on dehydration and rehydration. (5th September 2016) - Adalikwu, Stephen Adie; Chakraborty, Anindita; Hazra, Arpan; Ghosh, Dibyajyoti; Pati, Swapan K.; Maji, Tapas Kumar
Graphical abstract: Synthesis, single-crystal structure and magnetic properties of a 2D coordination compound [Ni(1, 3-ADA)(H2 O)] n (1 ) is reported which exhibits tunable magnetic behavior based on dehydration–rehydration.1 shows ferromagnetic (FM) interaction between Ni II ions. Combined experimental and theoretical studies reveal that FM interaction arises due to "orthogonal" magnetic orbitals, which become distorted in desolvated state and suppress the FM interaction. Abstract: Synthesis, single-crystal structure and magnetic properties of a 2D coordination compound [Ni(1, 3-ADA)(H2 O)] n (1 ) is reported which exhibits tunable magnetic behavior based on dehydration–rehydration.1 shows ferromagnetic (FM) interaction between Ni II ions. Combined detailed experimental and theoretical studies reveal that FM interaction arises due to "orthogonal" magnetic orbitals, which become distorted in desolvated state and suppress the FM interaction.